Modifying the structure KASUMI to improve its resistance towards attacks by inserting FSM and S-Box. Issue 1 (2nd January 2018) - Muthalagu, Raja; Jain, Subeen
ABSTRACT: In this paper, the strength of data confidentiality and integrity algorithms used in 3rd Generation Partnership Project (3GPP) mobile communication technologies are improved. KASUMI is a block cipher, which consists of eight Feistel rounds with a 128 – bit key. The confidentiality and integrity of 3G mobile communications systems depend on the security of KASUMI, which has been in place for more than 10 years. Literature survey reveals that it is possible to break KASUMI with a related key attack and very modest computational resources. To overcome the thread against the security attack, we proposed modification in the conventional KASUMI block cipher by inserting the finite state machine (FSM) followed by Rijndael S-box ( and ) at the end of the 7th round. The simulation results are provided in-terms of encryption speed and encryption time taken to show that the proposed modification in KASUMI does not affecting the speed of the encryption.